Towards a Synodal Church in Taiwan: Bringing Out New and Old Treasures - Chang, Jeffrey (Asian Horizons, 2025)
Mission is inextricably intertwined with the task of translation into the world’s various languages. After recounting some of the challenges of translating synodality terms and concepts into Chinese, this essay recalls some past lived experiences of synodality by Chinese-speaking Catholics in Taiwan. From those experiences of communion and mission, participation and power, resolutions and results, selected insights for synodality are offered.